Analisis Sisa Makanan untuk Mengevaluasi Kecukupan Asupan pada Lansia dan Menerapkan Pengendalian Mutu Manajemen Pelayanan Makanan di Panti Jompo Surabaya: Food Waste Assessment to Evaluate Adequacy Intake among Elderly and to Apply Quality Control of Food Service Management in Nursing Home - Farapti, Farapti; Rasyidah, Amira Farah; Kusumadewi, Salsabila Rahma; Dewi, Yulis Setiya; Hasanatuludhhiyah, Nurina; Winarno, Didik Dwi (Amerta Nutrition, 2024)
Background: Malnutrition is still common among the elderly, and meal provision has an important role in combating this issue. One of the meal provision programs is done by providing adequate quantity and quality of intake in nursing homes. Having less food waste can reflect to which extent intake and quality standards are applied in institutional food services. Objectives: This study aims to examine food waste as a factor in evaluating the adequacy of food intake and quality control in the food service management of nursing institutions. Methods: This study was conducted on 65 elderly at Surabaya Nursing Homes in 2023. Observations on the menu they had were carried out to determine the adequacy of their food intake. The Visual Comstock 7x hours method was used to assess the adequacy of food intake. Then, the food waste limit of 20% became a quality control in food service management. Results: The adequacy of nutritional intakes in the studied Surabaya nursing homes in terms of energy, carbohydrates, fiber, sodium, and potassium were 77.26%, 66.24%, 37.14%, 165.36%, and 27.17% of recommended daily allowance, respectively. This means that both the adequacy of the intake and the type of menu the elderly consumed are still below the standards. Food waste of more than 20% was identified from menus made of papaya, tongkol rica (spicy mackerel tuna), ote-ote (vegetable fritter), rice, green bean compote, sour vegetable soup, skipjack tuna balado (chili pepper skipjack tuna), and melon. Conclusions: The adequacy of food intake that the elderly consumed did not meet daily needs and recommendations. Apart from that, some menus still had >20% leftovers. The menu options need to be diversified to reach the recommended nutritional intake.